Person Equivalent Headcount Measures of Poverty - Tony Castleman; James Foster; Stephen C. Smith (Institute for the Study of Labor (IZA), 2015)
Headcount measures of poverty are by far the most common tools for evaluating poverty and gauging progress in global development goals. The headcount ratio, or the prevalence of poverty, and the headcount, or the number of the poor, both convey tangible information about poverty. But both ignore the depth of poverty, so they arguably present distorted views of the spatial distribution of poverty as well as the extent of progress against poverty over time. Additionally, headcount measures can provide incentives for policymakers and NGOs to focus their efforts on the least poor, an observation well understood among policymakers themselves. While other poverty measures mitigate these problems by capturing the intensity as well as the prevalence of poverty, they are often not central to policy discourse because they are perceived to be too "unintuitive" to have traction. There is a need for poverty measures that go beyond traditional headcount measures, but retain their direct interpretation. This paper presents person equivalent (p. e.) headcount measures, which do just that. Our approach draws on the logic of full-time equivalent jobs, adult equivalent incomes, and other constructs in economics. An initial period is used to calibrate the average depth of poverty among the poor, which then becomes the "person equivalent" underlying the p. e. headcount and the p. e. headcount ratio. We illustrate our methods using 1.25 a day poverty data from 78 countries as provided by the World Bank, and show how the new measures map out different pictures of poverty and progress than traditional headcount measures. Overall, the picture is one of a more rapid decline in global poverty, but with significant redistributions of its burden across regions and countries. For example, p. e. headcounts are much higher than traditional headcounts in Latin America and the Caribbean and Sub Saharan Africa; in South Asia and East Asia and the Pacific the reverse is true. In Kenya the traditional headcount rose by 8 million and the p. e. headcount rose by 11 million; in South Africa the p. e. headcount fell by more than the traditional headcount. We discuss properties of the new measures, outline some generalizations and conclude with recommendations for using this approach in development goals to track progress and direct policy.
Keywords: I32; O15; D63; 330; poverty measurement; headcount; poverty gap; FGT indices; development goals; inclusive growth; multidimensional poverty